Dimethyl Sulfate as Methylation Agent and Solvent in Highly Regioselective Synthesis of Methyl Salicylate Using Sodium Bicarbonate as a Base - de Souza Freitas, Milton; Nelson, David Lee; de Sousa, João Victor G.; Wentz, Alexandre P.; Tada, Dayane B.; Queiroz, Rafaela C.; Hurtado, Carolina R.; de Macedo, Erenilda F.; Conceição, Katia; Hurtado, Gabriela R. [UNESP]; Pessoa, Fernando L. P.; S Rodrigues, Yan Valdez; et al. (American Chemical Society (ACS), 2025)
Methyl salicylate (MS), the principal constituent of wintergreen oil, was obtained from salicylic acid (SA) by regioselective methylation of the carboxyl group. A new procedure involved exclusive capture of carboxylic hydrogen (−CO2H) through the use of the selective base, NaHCO3, and methylation via an SN2 mechanism employing the previously formed carboxylate as a nucleophile and the dimethyl sulfate [DMS] as the electrophilic reagent or substrate in a solvent-free reaction process. SA and NaHCO3 were added, followed by DMS after 30 min, and the reaction mixture was stirred at 90 °C for 90 min. The reaction was accompanied by thin-layer chromatography and gas chromatography. The conversion rate via GC was 100%, and the MS yield was 96%. The DMS used in excess was transformed into MeOH and H2SO4 when the mixture was washed with water. The MeOH was stored, and H2SO4 was transformed in Na2SO4 by neutralization with NaOH. The simplicity of the procedure, ready availability of MS, short reaction times, excellent yields, and mild reaction conditions are other advantages of this protocol. MS is being biologically tested as an antibacterial and antitumor agent. The focus of the study is on the search for drugs with greater selectivity for tumor cells so as to reduce adverse effects on normal cells because MS is rarely reported in the literature for this application. Cytotoxicities of 50 and 64% for cultured S. aureus and metastatic melanoma cells, respectively, were observed for a concentration of 0.6 mg/mL of the MS produced, whereas no cytotoxicity against nontumor cells was observed at this concentration. This is considered to be the optimum concentration.